Pewarisan Sifat Ketahanan Hidup dan Karakter Fenotipik Melon (Cucumis melo L. “TALITA” & “TANIA”) Hasil Persilangan Backcross dan Testcross Induk Tacapa Pada Kondisi Karst Secara In-Vivo - Riza Aristya, Ganiez; Arifiyanti, Roviqo; Rif'ah, Aziimatur (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2014)
Melon (Cucumis melo L.) is one of the fruits commodity priorities and require more attention. Plant breeding efforts led to improved varieties like TACAPA .TACAPA is a new melon cultivar derived from crosses between ♀ PI and ♂ Action with cross test PI. Since 2012, superior melon reassembled from crosses between ♀ TACAPA and ♂ PI become TANIA and ♀ TACAPA and ♂ Action become TALITA which projection can growth in critical lands karst. The objective of this research was to know ability to grow and morphological characteristics TALITA and TANIA melons were tested to determine nutrient levels of CaCO3. This research started from a field survey conducted in Hills of Mountain Sewu, South Mountain hills Sentolo Kulon Progo, and Dlingo Bantul, Yogyakarta.Melons grown on soil with fertilizer mixed media which further watering treated CaCO3 solution with a concentration of 0.5 % , 1%, 3%, 4%, and 5%. Observations were made until the time of harvest (± 10 weeks). TANIAand TALITA melon could grow on critical lands karst compared with parental. TANIA melonfruits have a weight, round, D - horizontal, D - vertical lower than two parental. TALITA melon fruits have a weight, D-horizontal higher than two parental, and D-vertical is lower than two parental.Keywords: critical land karst, Cucumis melo L., TALITA, TANIA